A Case Study on the Causes of Students' Reading, Writing, and Reading Comprehension Difficulties, According to Teachers' and Administrators' Views. - ÖZTÜRK, Cebrail (Mehmet Akif Ersoy University Journal of Education Faculty, 2026)
Literacy is a fundamental skill that, when acquired during the critical early years, enables individuals to succeed across multiple domains throughout life. However, students who fail to acquire literacy skills during primary school often face significant challenges in their subsequent academic and social lives. This study investigates the underlying causes of literacy and reading comprehension difficulties among students who failed to acquire literacy skills in first grade--a critical period for literacy development--and who were later identified as struggling with reading and writing in subsequent grades, based on the perspectives of teachers and school administrators. The study employed a qualitative case study design. Participants consisted of 15 teachers and 8 school administrators working at primary and lower secondary school levels, selected through maximum variation sampling. Data were collected throughout the 2023--2024 academic year using semi-structured interviews, monthly progress reports, and systematic classroom observations, and were analyzed using content analysis. Data were transcribed, followed by open coding to identify meaningful units; the resulting codes were grouped into categories and organized under overarching themes, with the constant comparative method applied throughout. The analysis revealed four main themes contributing to students' literacy acquisition difficulties: (1) personal factors, encompassing cognitive and emotional characteristics; (2) environmental factors, including family, school, and socio-economic context; (3) contextual factors, related to curricula and instructional materials; and (4) unforeseen factors, such as teacher changes and family crises. These four thematic domains highlight the multidimensional and interconnected nature of literacy difficulties, indicating that effective intervention strategies should simultaneously address individual, environmental, and contextual factors. The findings underscore the importance of early identification and support mechanisms and offer implications for teacher education programs.